2007
DOI: 10.1002/app.27519
|View full text |Cite
|
Sign up to set email alerts
|

Influence of natural fiber type in eco‐composites

Abstract: This study concerns the preparation of ecocomposites based on natural fibers coming from wood and subproducts (rice husks) and products (kenaf) of annually grown plants. The matrices used were of two types: a biopolymer (PLA) and a petroleum-derived polymer (HDPE). Results showed that natural fibers markedly increase the tensile and flexural properties of both polymers by extending the field of application of these materials with less use of nonrenewable resources. The properties obtained are comparable to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 26 publications
3
62
0
4
Order By: Relevance
“…In general, adding natural fibers to polymers increases its brittle character, normally changing its strain behavior; an interesting result obtained in this work was the increase in HDT values of cotton nanolinter compounds with no change in strain at break values (see Figure 6). This increase in HDT values indicates that the acid hydrolysis was successful, and may result in an increase in the use temperature of PCL products 39,[41][42] . for supplying the cotton nanolinter, and to Federal University of São Carlos Polymer Laboratory for HDT experiments.…”
Section: Acknowledgmentsmentioning
confidence: 95%
“…In general, adding natural fibers to polymers increases its brittle character, normally changing its strain behavior; an interesting result obtained in this work was the increase in HDT values of cotton nanolinter compounds with no change in strain at break values (see Figure 6). This increase in HDT values indicates that the acid hydrolysis was successful, and may result in an increase in the use temperature of PCL products 39,[41][42] . for supplying the cotton nanolinter, and to Federal University of São Carlos Polymer Laboratory for HDT experiments.…”
Section: Acknowledgmentsmentioning
confidence: 95%
“…There has been a growing interest in the development of environmentally benign composites based on biodegradable poly(lactic acid) (PLA) polymer and various lignocellulosic materials such as kenaf [1,2], flax [3], hemp [4], bamboo [5,6], wood fibers [7], and reed fibers [8]. Addition of lignocellulosic materials in PLA is intended to improve the properties of this polymer without compromising its biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of lignocellulosic materials in PLA is intended to improve the properties of this polymer without compromising its biodegradability. Although there has been very little work in the development of biodegradable polymer composites using rice hulls [1], several studies have demonstrated the potential of rice hulls in polymer composites [9][10][11][12][13]. Rice hulls are siliceous lignocellulosic residues, which have moderate water resistance and stability against degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a good economic practice, the use of natural fibers can also reduce the use of products are difficult to decompose 2,3 . The use of vegetable fibers as a reinforcement in composite materials boasts a number of advantages: a great potential to improve the performance of the polymers in technological applications 4,5 , a lessening of the environmental impact of its production 6 , relatively low costs, the abundance of such fibers, and the potential biodegradability under suitable environmental conditions 4,5 .…”
Section: Introductionmentioning
confidence: 99%